2015
DOI: 10.2355/isijinternational.55.934
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Interaction between Chromium and Sulfur in High Cr Containing Liquid Iron

Abstract: Thermodynamic interaction between chromium and sulfur in liquid iron was studied using the slag/ metal equilibration technique to measure the effect of chromium on the equilibrium sulfur distribution between the slag and carbon saturated Fe-Cr-S alloys containing chromium up to 30 mass% in the temperature range from 1 823 K to 1 923 K. The sulfide capacity of the CaO-Al2O3 slag was separately determined using carbon saturated liquid Fe-S alloys under CO atmosphere as a function of temperature. The sulfur distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results of this section of experiments are in agreement with the outcome of other references dealing with high-temperature H 2 S decomposition, 29 H 2 S reaction to metal oxides, 30,31 and H 2 S-iron interactions. 32 Do et al 33 examined the effect of Cr in Fe─C─S systems in 1550-1650 C, and the results showed that the sulfide ion (S 2− ) is transferred to the metal framework as an ultrastable compound leading to less H 2 S emission. Radenovic 34 studied the chemical shift of organo-sulfur compounds in the petroleum coke upon heating to 1500 C, 2000 C, and 2400 C, and the reaction time was set to 2 and 4 hr.…”
Section: Effect Of Final Temperaturementioning
confidence: 99%
“…The results of this section of experiments are in agreement with the outcome of other references dealing with high-temperature H 2 S decomposition, 29 H 2 S reaction to metal oxides, 30,31 and H 2 S-iron interactions. 32 Do et al 33 examined the effect of Cr in Fe─C─S systems in 1550-1650 C, and the results showed that the sulfide ion (S 2− ) is transferred to the metal framework as an ultrastable compound leading to less H 2 S emission. Radenovic 34 studied the chemical shift of organo-sulfur compounds in the petroleum coke upon heating to 1500 C, 2000 C, and 2400 C, and the reaction time was set to 2 and 4 hr.…”
Section: Effect Of Final Temperaturementioning
confidence: 99%